Performance of lactating cows fed processed grain sorghum and expeller soybean meal - Evan C. Titgemeyer; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1995)
Forty-four Holstein cows were used to measure milk production responses to dryrolled vs processed grain sorghum and expeller vs solvent soybean meal (SBM) in a 2x2 factorial arrangement of four treatments. Processing of grain sorghum decreased feed intake 5%, but increased milk by 3%, protein by 4%, and efficiency by 7%, with fat being unaffected. Replacement of solvent SBM with expeller SBM had little effect on intake, but increased milk by 3%, fat by 5%, and efficiency by 4%, with protein being unaffected. The processing of grain sorghum seems to be a valuable method to improve its nutritive value for lactating cows. Total milk and fat yield, but not protein yield, were increased in response to feeding expeller SBM in the place of solvent SBM.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Expeller soybean meal; grain sorghum; Cows